2020
DOI: 10.3390/su12020695
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Dual Ecological and Well-Being Benefits from an Urban Restoration Project

Abstract: The degradation of urban natural spaces reduces their ability to benefit human populations. Restoration can support urban sustainability by improving both the ecological health of these spaces and the public benefits they provide, but studies rarely combine both perspectives. We assessed the ecological and social benefits of an urban river restoration project relative to an unrestored river on the basis of the following four principles: Increasing ecological integrity; benefitting and engaging society; taking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 59 publications
(117 reference statements)
0
25
0
1
Order By: Relevance
“…The seepage flow into the lake and seepage losses to the downstream were calculated by equation: (4) where: K -hydraulic conductivity, m/s; d -distance between river and lake, m; L -seepage length, m; H 1 , H 2 -water level in the river and lake, m. The culvert was taken as the water intake structure. The discharge was calculated by equation: (5) where: Q -water discharge, m 3 /s; φ -velocity coefficient; w c -flow area, m 2 ; H 1 , H 2water head at the entrance and outlet of the intake structure, m. The water intake structure supplies water from the river to the lake during the low water period. The water intake is closed by the gate to prevent getting turbid water and debris from the river to the lake and to preserve local biodiversity during an extreme flood.…”
Section: Study Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The seepage flow into the lake and seepage losses to the downstream were calculated by equation: (4) where: K -hydraulic conductivity, m/s; d -distance between river and lake, m; L -seepage length, m; H 1 , H 2 -water level in the river and lake, m. The culvert was taken as the water intake structure. The discharge was calculated by equation: (5) where: Q -water discharge, m 3 /s; φ -velocity coefficient; w c -flow area, m 2 ; H 1 , H 2water head at the entrance and outlet of the intake structure, m. The water intake structure supplies water from the river to the lake during the low water period. The water intake is closed by the gate to prevent getting turbid water and debris from the river to the lake and to preserve local biodiversity during an extreme flood.…”
Section: Study Methodsmentioning
confidence: 99%
“…The river restoration projects face significant challenges related to the need to combine the natural environment and comfortable living on the urban area. In the work by [ De Bell et al 2020] it was assessed the restoration of the Medlock and Irk rivers (UK) in terms of biological and social indicators, which showed that from an ecological point of view, the states of the restored areas of the rivers were improved significantly. The social assessment of the restored areas was differed: citizens were pleased by natural river state, but demanded social infrastructure near the rivers and the preservation of historical heritage elements.…”
Section: Introductionmentioning
confidence: 99%
“…Finding ways to address this relation between local residents and UGI is especially relevant to those studying and holding responsibility for the built environment [28], resource management, public health, or agents considering interventions aimed to support the well-being of individuals and communities. In addition, and given the current context of growing valorization of 'non-expert' (or non-technical) knowledge as valuable input in placemaking processes, uncovering local narratives and perspectives seems particularly pertinent [29]. Especially since the European Landscape Convention defined 'landscape' as "an area, as perceived by people, whose character is the result of the action and interaction of natural and/or human factors" [30].…”
Section: Green Spaces Local Perception and Well-beingmentioning
confidence: 99%
“…Although urban demands can be added to a river restoration project, the waterfront design mainly aims to recover social relations and urban function between the river and the city in their interface line of contact. In fact, therefore, there is an opportunity to step further and to use the river restoration approach to improve not only the fluvial environment but also the city, considering the city as an adapting organism in constant transformation and capable of embracing both demands (natural and urban), while involving the population in the process [21]. In this way, it is desirable to search for ways to rethink the relation between rivers and cities, supporting urban river restoration in a comprehensive way, with multiple benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Joining these two concepts-urban river restoration and sustainable urban drainage-can provide a consistent path towards a more sustainable solution for urban floods, with additional benefits. Urban river restoration, although usually limited by the heavy modifications introduced in the urban watershed, has the potential to improve the environmental quality of the river and provide opportunities for urban revitalization [19,21]. However, it is necessary to integrate this approach with distributed actions in the watershed to recover hydrological functions that were modified by the urbanization process itself [27].…”
Section: Introductionmentioning
confidence: 99%